The Relationship Between Whole Grain Intake and Body Weight: Results of Meta-analyses of Observational Studies and Randomized Controlled Trials (FS18-07-19). (13th June 2019) - Maki, Kevin; Palacios, Orsolya; Koecher, Katie; Sawicki, Caleigh; Livingston, Kara; Bell, Marjorie; McKeown, Nicola
Abstract: Objectives: To analyze data from observational studies and randomized controlled trials (RCTs) reporting on the relationship between whole grain (WG) intake and weight status. Methods: A systematic literature search was conducted, using Ovid/Medline, to identify observational studies and RCTs assessing WG food intake and weight status in adults. Meta-regression analysis was used to derive pooled estimates from cross-sectional studies, and a meta-analysis with random effects modeling was used to derive pooled estimates from RCTs. Prospective cohort results were assessed qualitatively since differences in methods and outcomes prevented completion of a pooled analysis. Results: Eleven publications (12 studies; 136, 834 subjects) were included in the meta-regression analysis of cross-sectional data, 8 publications (9 studies; 973 subjects) were included in the meta-analysis of RCTs, and 6 publications were reviewed for qualitative assessment of prospective cohort data. RCT intervention lengths ranged from 12–16 weeks, and WG intake from foods ranged from 32–215 g/d in the WG intervention groups. Meta-regression of cross-sectional studies indicated a significant, inverse correlation between body mass index (BMI) and intake of WG from food: weighted slope −0.0141 kg/m 2 per g/d [95% confidence interval (CI): −0.0207, −0.0077; r = −0.526, P = 0.0001]. Meta-analysis of data from RCTs showed a non-significant pooled standardized effect size of −0.049 kg (95% CI −0.297, 0.199, P = 0.698) for the mean difference in weight change for the WG intervention groups compared with controls. No significant differences were observed for secondary variables, including waist circumference and % body fat. Prospective cohort results generally showed inverse associations between weight change and baseline WG intake and change in WG intake over follow-up periods of 5 to 20 years. Conclusions: Higher WG intake is significantly inversely associated with BMI in observational studies, but results from RCTs do not show an effect of WG intake on change in weight over periods of up to 16 weeks. RCTs with longer intervention periods are needed to further investigate the potential for WG intake to influence body weight and related anthropometrics. Funding Sources: General Mills, Inc., Minneapolis, MN.